Lebanon Shiite Woman in the Middle of Discrimination Feminist Literary Criticism Analysis of the Novel Hikayah Az-Zahra - Betty Mauli Rosa Bustam (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
This article reveals a picture of discrimination against women that occurs in a Shiite Muslims community in Lebanon. As is well known, Shi'a Muslims are second only to Sunnis in Lebanese Muslims as a whole, even though both populations are balanced. Islam itself became the second religion after Christianity in Lebanon and there are still several other religions (sects). Lebanon accommodates the growth of many religions that have a variety rules for their followers, so there is often attraction in making decisions regarding state laws and regulations, especially relating to women. Feminist Literary Criticism is used to explain all literary phenomena relating to women that aesthetically spread in the Hikayah az-Zahra novel which is the object of the research, this is due to the peculiarities of women which can only be explained using their own perspective. The results of this study will show a variety of forms of discrimination against women in Shiite circles, which are part of the daily lives of Lebanese people in situations of prolonged conflict. Shiite women, represented by the character of Zahra, cannot even expect protection from anywhere, including family members.